Synthesis and characterization of silicon phthalocyanines bearing axial phenoxyl groups for attachment to semiconducting metal oxides - Bergkamp, Jesse J. (2011)
A series of axial phenoxy substituted octabutoxy silicon phthalocyanines bearing ethyl carboxylic ester and diethyl phosphonate groups have been prepared from the corresponding phenols in pyridine. Axial bis-hydroxy silicon phthalocyanine was prepared using an adaptation of a reported protocol [1, 2] from the octabutoxy free-base phthalocyanine. The phenols bear either carboxylic ester or phosphonate groups, which upon deprotection can serve as anchoring groups for attaching the phthalocyanines to semiconducting metal oxides used in dye sensitized solar cells (DSSCs). All the phthalocyanines of the series absorb in the near infra-red region: 758-776 nm. The first oxidation potential for each phenoxy derivative occurs near 0.55 V vs. SCE as measured by cyclic voltammetry, with all falling within a 10 mV range. This indicates that these dyes will have sufficient energy in the photo-excited state to drive the reduction of protons to hydrogen. Taking into account the absorption and electrochemical potentials, these dyes are promising candidates for use in dual-threshold photo-electrochemical cells.